59. Nomenclatural notes on saline vegetation of Ukraine, southern Russia and Kazakhstan. - Lysenko, Tatiana; Mucina, Ladislav; Iakushenko, Dmytro (Lazaroa, 2011)
In this syntaxonomic nomenclature note we introduce the Plantagini salsae-Artemision santonici (Artemisio santonicae- Limonietalia gmelinii, Festuco-Puccinellietea), a new name for the syntaxon carrying an illegitimate name ‘Artemision santonici Shelyag-Sosonko & Solomakha 1987’. This vegetation comprises Artemisia santonicum dominated salt-steppe vegetation on solonetz-like soils of slightly elevated habitats of alluvial plains and of the slopes of shallow depressions in the steppe zone of Ukraine and forest-steppe and steppe zones of Russia. We also suggest a nomenclatural adjustment (nomen inversum) for the ‘Artemisio pauciflorae-Camphorosmion monspeliacae' (Artemisietalia pauciflorae, Festuco- Puccinellietea). The steppe vegetation classified within this latter syntaxon occurs in southern Russia and northern Kazakhstan.